Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1182/blood.2020006578
|View full text |Cite|
|
Sign up to set email alerts
|

A phase 2 study of venetoclax plus R-CHOP as first-line treatment for patients with diffuse large B-cell lymphoma

Abstract: The phase II CAVALLI (NCT02055820) study assessed efficacy and safety of venetoclax, a selective, B-cell lymphoma-2 (Bcl-2) inhibitor, with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in first-line (1L) diffuse large B-cell lymphoma (DLBCL), including patients demonstrating Bcl-2 protein overexpression by immunohistochemistry (Bcl-2 IHC-positive). Eligible patients ≥18 years with previously untreated DLBCL, Eastern Cooperative Oncology Group performance status ≤2, and Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 36 publications
0
64
0
Order By: Relevance
“…Given that venetoclax is being tested in combination with other chemotherapies, such as rituximab, cyclophosphamide, doxorubicin, and vincristine (components of RCHOP) in DLBCL [ 31 ] and bendamustine-rituximab in FL [ 32 ], we determined whether exposure to frontline chemotherapy drugs could bring cells closer to the apoptotic threshold and synergize with venetoclax to initiate apoptosis. Since the supply of primary lymphoma cells is limited, and their growth and viability are poor ex vivo over long periods of culture, we performed BH3 profiling on HGBL-DH cell lines after exposure to different chemotherapies in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that venetoclax is being tested in combination with other chemotherapies, such as rituximab, cyclophosphamide, doxorubicin, and vincristine (components of RCHOP) in DLBCL [ 31 ] and bendamustine-rituximab in FL [ 32 ], we determined whether exposure to frontline chemotherapy drugs could bring cells closer to the apoptotic threshold and synergize with venetoclax to initiate apoptosis. Since the supply of primary lymphoma cells is limited, and their growth and viability are poor ex vivo over long periods of culture, we performed BH3 profiling on HGBL-DH cell lines after exposure to different chemotherapies in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…RCHOP and venetoclax should be effective in high-grade lymphomas that express BCL2 protein, are not class B, and co-depend on BCL2 and MCL1 (53% of our diagnostic DLBCL samples). This combination appeared to translate into a clinical benefit in patients with BCL2+ DLBCL in the phase II CAVALLI study [ 31 ]. Thus, BH3 profiling could be used to predict patients’ responses to venetoclax and select drugs that could be synergistic.…”
Section: Discussionmentioning
confidence: 99%
“…Double expressor lymphoma is high expression of BCL2 and MYC protein by immunohistochemistry, cutoff of which is 50% and 40% respectively. There are several studies reporting the outcomes of BCL2 inhibitor combined chemotherapy as rst or salvage therapy for refractory or relapse DLBCL [14][15][16]. One prospective phase II study found trend was observed for improved investigator-assessed PFS for venetoclax plus R-CHOP as a front-line therapy in the BCL2 IHC-positive subgroups (HR = 0.55, 95% CI, 0.34-0.89), compared with R-CHOP [16].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies reporting the outcomes of BCL2 inhibitor combined chemotherapy as rst or salvage therapy for refractory or relapse DLBCL [14][15][16]. One prospective phase II study found trend was observed for improved investigator-assessed PFS for venetoclax plus R-CHOP as a front-line therapy in the BCL2 IHC-positive subgroups (HR = 0.55, 95% CI, 0.34-0.89), compared with R-CHOP [16]. However, ORR of BCL2 inhibitor monotherapy for relapsed/refractory DLBCL is only 15%-18% without details of BCL2 protein expression [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…These classifications may complement conventional prognostic scores, such as the international prognostic index (IPI), in identifying high-risk subsets of patients [16]. The importance of understanding the heterogeneity in DLBCL was illustrated by several studies that identified subgroups of high-risk patients that could benefit from associating targeted therapy to standard treatment, emphasizing the significance of a personalized medicine approach [17][18][19].…”
Section: Introductionmentioning
confidence: 99%